Improvement of Endovascular Stroke Treatment: A 24-Hour Neuroradiological On-Site Service Is Not Enough. (4th January 2018) - Nikoubashman, Omid; Schürmann, Kolja; Othman, Ahmed E.; Bach, Jan-Philipp; Wiesmann, Martin; Reich, Arno
Abstract : Background and Purpose . With the advent of endovascular stroke treatment (EST) with mechanical thrombectomy, stroke treatment has also become more challenging. Purpose of this study was to investigate whether a fulltime neuroradiological on-site service and workflow optimization with a structured documentation of the interdisciplinary stroke workflow resulted in improved procedural times. Material and Methods . Procedural times of 322 consecutive patients, who received EST (1) before (n = 96 ) and (2) after (n = 126 ) establishing a 24-hour neuroradiological on-site service as well as (3) after implementation of a structured interdisciplinary workflow documentation ("Stroke Check") (n = 100 ), were analysed. Results . A fulltime neuroradiological on-site service resulted in a nonsignificant improvement of procedural times during out-of-hours admissions (p ≥ 0.204 ). Working hours and out-of-hours procedural times improved significantly, if additional workflow optimization was realized (p ≤ 0.026 ). Conclusions . A 24-hour interventional on-site service is a major prerequisite to adequately provide modern reperfusion therapies in patients with acute ischemic stroke. However, simple measures like standardized and focused documentation that affect the entire interdisciplinary pre- and intrahospital stroke rescue chain seem to be important.